Pelatihan Elektronika Dasar Untuk Guru dan Siswa kelas VII Di SMP Kristen Harapan Bagi Bangsa- Cilincing Jakarta Utara - Ghozali, Theresia; Wijayanti, Linda; Mahyastuti, V. Winda; Lukas, Lukas; Mulyadi, Melisa (Jurnal Pengabdian Masyarakat Charitas, 2023)
SMP Kristen Harapan Untuk Bangsa is located on Jl. Kebantenan I no 10, Cilincing, North Jakarta. According to Basic Education and Culture Data (DAPOKDIKBUD), this school has 9 teaching staff. This school is also equipped with one science and computer laboratory to support the teaching and learning process . Most of the students of SMPK Kristen Harapan Bagi Bangsa come from lower-middle economic families. This condition makes students from this school not easy to get the opportunity to take courses outside school hours, due to economic difficulties . For this reason, the role of the school is expected so that students from this school still have the opportunity to enrich knowledge through learning outside school hours, namely in the form of extra-curricular activities. In order for students to have the knowledge to be able to choose a Vocational High School that suits students' talents and interests, the school facilitates extracurricular activities of Basic Electronics training. In June 2023, the Electrical Engineering Study Program, Faculty of Engineering, Atma Jaya Catholic University held a community service program with the skills taught were component introduction, measuring instrument reading techniques and making LED light circuit modules. Soldering training and making Light Emitting Diode modules were conducted for 3 days. From the results of the questionnaire, it can be seen that students are enthusiastic and claim to have gained knowledge from this training.